2016
DOI: 10.3389/fpsyg.2016.01666
|View full text |Cite
|
Sign up to set email alerts
|

Can Touch Screen Tablets be Used to Assess Cognitive and Motor Skills in Early Years Primary School Children? A Cross-Cultural Study

Abstract: Assessment of cognitive and motor functions is fundamental for developmental and neuropsychological profiling. Assessments are usually conducted on an individual basis, with a trained examiner, using standardized paper and pencil tests, and can take up to an hour or more to complete, depending on the nature of the test. This makes traditional standardized assessments of child development largely unsuitable for use in low-income countries. Touch screen tablets afford the opportunity to assess cognitive function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
42
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 67 publications
(90 reference statements)
6
42
1
Order By: Relevance
“…The administration of standardized computer‐based tasks constitutes one possible approach to limiting effects of methodological thresholds. Studies assessing reliability and validity of cognitive tasks, such as visual attention and short‐term memory, offer support for the notion that this form of assessment presents a promising approach to cross‐cultural assessment (Pitchford & Outhwaite, ).…”
Section: Discussionmentioning
confidence: 97%
“…The administration of standardized computer‐based tasks constitutes one possible approach to limiting effects of methodological thresholds. Studies assessing reliability and validity of cognitive tasks, such as visual attention and short‐term memory, offer support for the notion that this form of assessment presents a promising approach to cross‐cultural assessment (Pitchford & Outhwaite, ).…”
Section: Discussionmentioning
confidence: 97%
“…Until recently, developmental researchers studying young children in LMIC have primarily focused on measuring general cognitive skills (Aboud & Yousafzai, ). Given the growing interest in directly assessing children's EFs in LMIC (Obradović, Yousafzai, et al., 2016; Oluwole, Noll, Winger, Akinyanju, & Novelli, ; Pitchford & Outhwaite, ; Wolf & McCoy, ), it is important to understand how antecedent cognitive skills relate to emergent EFs. Using the widely employed Bayley Scales of Infant and Toddler Development, we found that direct assessments of general cognitive skills at 24 months were significantly related to children's performance on EF tasks at 48 months.…”
Section: Discussionmentioning
confidence: 99%
“…Many challenges arise when researchers employ tests developed and validated with children living in HIC to assess cognitive skills of children in LMIC (see Pitchford & Outhwaite, 2016;Zuilkowski, McCoy, Serpell, Matafwali, & Fink, 2016). We want to highlight three issues in conducting EF assessments with preschool children in rural LMIC settings at scale.…”
Section: Assessment Of Executive Functioning In Lmic Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…Metrics such as game accuracy and completion time have been shown to differ according to difficulty of the task and age of participants [42]. The potential utility of these gamified tablet-based tasks for cognitive assessment in young children is further supported through preliminary evidence of their reliability and validity against gold standard assessments of child development [43,44].…”
Section: Introductionmentioning
confidence: 99%